Chemotaxonomic significance of phenylpropanoids from Styrax suberifolius Hook. Et Arn. (June 2018) - Liu, Binglei; Ding, Wenbing; Huang, Shuying; Sun, Weihua; Li, Youzhi
Abstract: The first phytochemical investigation of the bark of Styrax suberifolius Hook. Et Arn. (Styracaceae) successfully isolated and identified seventeen phenylpropanoids, including ten benzofuran derivatives (1–10 ), two ditetrahydrofurans (11 and12 ), two neolignans (13 and14 ) and three phenyl alkanols (15–17 ). Compounds 2-(3-hydroxy-4-methoxyphenyl)-7-methoxy-5-benzofuranpropa- nol (5 ), (+)-cedrusin (6 ), (−)-(7R, 8 S )-dihydrodehydrodiconiferyl alcohol 4- O -β-d - glucopyranoside (8 ), (−)-(7 S, 8R)-dihydrodehydrodiconiferyl alcohol 4- O -β-d - glucopyranoside (9 ), (+)-(7 S, 8R)-dihydrodehydrodiconiferyl alcohol (10 ), (+)-(7 S, 8R) -erythro-4, 7, 9, 9′-tetrahydroxy-3, 3′-dimethoxy-8- O -4′-neolignan (13 ), (−)-symplocos- neolignan A (14 ), (−)-7- O -ethylguaiacylglycerol (15 ), 2-[4-(3-hydroxypropyl)-2- methoxyphenoxy]-1, 3-propanediol (16 ) and dihydroconiferyl alcohol (17 ) have not been recorded in Styrax Linn. previously. The chemotaxonomic significance of isolated compounds is discussed. Highlights: The first phytochemical investigation of Styrax suberifolius Hook. Et Arn. obtained seventeen phenylpropanoids. Compounds5, 6, 8–10 and13–17 were isolated from Styrax Linn. for the first time. The chemotaxonomic significance of isolated phenylpropanoids was discussed.